The Anthaxia (Anthaxia) manca (Linnaeus, 1767) species-group in Iran, with description of a new species and a new synonymy (Coleoptera: Buprestidae) - Baiocchi, Daniele (Zootaxa, 2013)
Anthaxia (Anthaxia) simandli sp. nov., a new endemic species from Iran is described, together with the hitherto unknown male of Anthaxia (Anthaxia) magnifica Bílý, 1983. New synonymy of Anthaxia (Anthaxia) mancatula Abeille, 1900 = Anthaxia (Anthaxia) intermedia Obenberger, 1913 syn. nov. is proposed, and a lectotype for A. mancatula is designated. All species are illustrated, and comments on their bionomy, distribution, and taxonomic position are given, as well as on the current state of the Anthaxia (Anthaxia) manca (Linnaeus, 1767) species-group in Iran.